Analysis Digital Transformation in SMEs: Insights into Adoption Process, Employees Digital Proficiency and Concerns from Managerial Perspective - Leslie, Kellie; Deu, Indasari; Eryc, E (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Batam City has recognized the benefits of digital transformation and has actively adopted digital technology. However, it is a misconception to view digital transformation as merely the adoption of new technologies. To digitally transform a business, SMEs need to acquire managerial capabilities and digital proficiency of employee. The need to ensure that managers and employees are equipped with the digital knowledge is essential. Delays in addressing these issues could result in a broader digital gap, putting Batam's SMEs at a disadvantage in both local and global markets. The study employs a qualitative approach through in-depth interviews with SME owners or managers. The findings show that while digital transformation improves operational efficiency, market reach, innovation, and reducing fraud, SMEs face challenges such as limited capabilities, skills gaps, and emerging market demands. The study shows that managerial skills and employee readiness are key in ensuring a successful digital transformation. This research provides a practical overview for entrepreneurs or managers to help them navigate digitalization in a dynamic environment.